Kubus Augmented Reality (AR) 3D Sebagai Media Pembelajaran Inovatif untuk Meningkatkan Maharah Kalam Mahasiswa Generasi Z / 3D Augmented Reality (AR) Cubes as Innovative Learning Media to Improve the Speaking Skills of Generation Z Students - Devi Eka Diantika; Ahmad Amirul Kholid (Universitas Islam DDI AGH Abdurrahman Ambo Dalle Polewali Mandar, Sulawesi Barat, 2026)
Generation Z, as digital natives, requires interactive, visual, and engaging learning media—particularly for developing Arabic speaking skills, which students often find challenging. This study aims to develop and evaluate the effectiveness of a 3D Augmented Reality (AR) Cube as an innovative learning medium to enhance Arabic speaking proficiency among university students. Using the ADDIE-based Research and Development (R&D) model, the study was conducted with 38 students from the Arabic Language and Literature Study Program at UNUGIRI over four weeks (eight sessions). Data were collected through expert validation, student response questionnaires, classroom observation, and pre-test/post-test assessments. Results show that the AR Cube was rated